New Pyrethroids for Use Against Tuta Absoluta (Lepidoptera: Gelechiidae): Their Toxicity and Control Speed. Issue 5 (30th September 2017) - Moreno, Shaiene C; Silvério, Flaviano O; Picanço, Marcelo C; Alvarenga, Elson S; Pereira, Renata R; Santana Júnior, Paulo A; Silva, Gerson A
Abstract: Insect pests are responsible for major losses in crop productivity, and insecticides are the main tools used to control these organisms. There is increasing demand for new products for pest management. Therefore, the aim of this study was to assess the toxicity of pyrethroids with acid moiety modifications to measure the insecticidal activity of these compounds on Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). First, we synthesized E/Z mixtures of five pyrethroids: [9], [10], [11], [12], and [13]. Then, we separated the cis and trans pyrethroid isomers of [9], [10], [11], and [12]. We assessed the toxicity of these compounds against T. absoluta. The E/Z mixtures of the five pyrethroids (30 µg of substance per mg −1 of insect) caused high (100%) and rapid (<12 h) tomato borer mortality. The cis isomer of pyrethroid [10] was the most toxic to T. absoluta, causing mortality similar to permethrin. The other isomers were less powerful than permethrin.